PROGRAM KEMITRAAN MASYARAKAT PEMBERDAYAAN KELOMPOK BERESIKO DALAM MENINGKATKAN KEMANDIRIAN PENGELOLAAN MANAJEMEN DIABETES MELLITUS TYPE II DALAM UPAYA PENCEGAHAN KOMPLIKASI DI WILAYAH MOJOLANGU KOTA MALANG - Lundy, Fiashriel; Halis, Farida; Aisyah, Siti (Jurnal IDAMAN (Induk Pemberdayaan Masyarakat Pedesaan), 2025)
Abstract: Diabetes Mellitus (DM) Type 2 is a metabolic disease that is growing rapidly in the world, including Indonesia. This disease can cause various serious complications if not managed properly, such as heart disease, kidney damage, and visual impairment, which not only reduce the quality of life of sufferers but also increase the economic burden on families and communities. Currently, public awareness of the importance of prevention and proper management of diabetes is still low. Many sufferers are not aware of the importance of healthy lifestyle changes, such as maintaining a balanced diet, regular physical activity, and routine health checks. In fact, diabetes complications can actually be prevented with early detection and effective management. Community empowerment, especially at-risk groups, is an important approach to improving knowledge and skills in diabetes management, while encouraging active participation from various parties, including families, communities, and health workers. Through counseling, independent training, and community-based programs, the community is encouraged to independently prevent complications and create an environment that supports a healthy lifestyle, one of which is the Community Partnership Program for Empowering Risk Groups in Increasing Independence in Managing Type II Diabetes Mellitus Management in Efforts to Prevent Complications at the Mojolangu Health Center, Mojolangu Village, Malang City.. Keywords: empowering, DM Type II, complications